Comparative effectiveness of erenumab versus oral preventive medications among migraine patients: A US claims database study - Stewart J Tepper; Juanzhi Fang; Lujia Zhou; Pamela Vo; Ahmad Abdrabboh; Mrudula Glassberg; Matias Ferraris (SAGE Publishing, 2021)
Background: Erenumab, a fully human monoclonal antibody targeting the calcitonin gene-related peptide pathway, was developed specifically for preventive treatment of migraine. Objective: To compare the real-world effectiveness of erenumab and non-specific oral migraine preventive medication (OMPM) on acute medication usage and healthcare resource utilization (HCRU) among migraine patients. Methods: This retrospective US claims analysis included patients (≥18 years) diagnosed with migraine who initiated erenumab (May 01, 2018 and September 30, 2019) or OMPM (May 01, 2016 and October 31, 2017). Cohorts were matched 1:1 using the propensity score (PS) method with stratification. Acute medication usage, HCRU, and a composite endpoint of 1) outpatient visit with a migraine diagnosis and associated acute medication claim, 2) hospital admission with a primary migraine diagnosis, or 3) emergency room visit with a primary migraine diagnosis were assessed 6 months post-treatment initiation. Results: Following PS matching, both cohorts included 2,343 patients. At 6 months, erenumab was associated with significantly less acute medication usage versus OMPM, including number of types of acute medications used, number of claims per person, and proportion of patients using acute medication. HCRU and number of composite events were also significantly lower among erenumab users. Conclusion: Erenumab is more effective than OMPM at reducing acute medication usage and HCRU among migraine patients. Trial registration: N/A.